Economic challenges for the contemporary world : essays in honour of Prabhat Patnaik - Das, Mausumi; Kar, Sabyasachi; Nawn, Nandan; Patnaik, Prabhat (Sage, 2016)
Cutting-edge scholarship on various aspects of economic development!